Game-Based rehabilitation program for community-based centers in Malaysia - Latif R.A.; Ismail R.; Mohd Mahidin E.M. (Insight Society, 2023)
Rehabilitation and intervention therapy is a program medically structured for disabled patients due to unfortunate events or born with disabilities. Rehabilitation and intervention therapy require prolonged, continuous, and intensive recovery activities that can be time-consuming, difficult, costly, and tedious. Based on studies conducted, rehabilitation and intervention programs are not well-received by many patients due to some reasons. Hence, innovative home-based and community-based rehabilitation and intervention programs are to be advocated and endorsed to engage these disabled patients continuing their required treatments for better success in rehab. Focus groups consist of three community-based rehabilitation centers in Putrajaya, Malaysia, were studied; the goal is to investigate the objectivity of current rehabilitation and intervention programs held. Rehabilitation and intervention programs conducted are designed and implemented based on the disability types of each patient (trainees), executed by teachers, and also professional therapists. Among the many programs held, it had been identified that for revamp; it can be done within one of the programs, which will boost the current rehabilitation and intervention program; the focus should be at the Prepare for School program. The program focuses on younger trainees (aged 5-9 years old), preparing them to enter school. The program uses multimedia courseware as one medium of delivery. Respondents highly recommended that there is a need to infuse and improve the current game elements within the courseware. The change is imperative and necessitated for community-based rehabilitation and intervention program. 2020 Insight Society.